Real-world safety profile of zanubrutinib: a disproportionality analysis based on the FAERS database - Ping Huang; Xiaochun Zheng; Miaomiao Zhang; Jiangfeng Wang; Jingyang Lin; Jinlong Huang; Xiuli Yang (BMJ Open)
Objective Zanubrutinib is a second-generation Bruton’s tyrosine kinase inhibitor that has been approved for the treatment of several B cell malignancies. The aim of this study was to evaluate adverse events (AEs) associated with zanubrutinib based on the real-world data.Design A disproportionality analysis was performed to identify the potential zanubrutinib-related AEs.Setting The Food and Drug Administration AE Reporting System database from the fourth quarter of 2019 to the third quarter of 2023.Main outcome measures The results of the disproportionality analyses were presented as reported ORs (RORs). When the lower limit of the 95% CI for the ROR is greater than 1 and the number of AE reports is≥3, it indicates that the preferred term (PT) may be a positive AE signal.Results A total of 846 AE reports with zanubrutinib as the primary suspect drug were obtained, with 2826 AEs. A total of 74 positive PT signals were detected across 18 system organ classes (SOCs). The most significant signal for SOC was ‘blood and lymphatic system disorders’ (ROR=2.8, 95% CI 2.3 to 3.3), while the most significant signal for PT was ‘haemorrhage subcutaneous’ (ROR=190.8, 95% CI 128.0 to 284.5). 13 unexpected off-label AEs were also observed, such as abnormal hair texture, skin discolouration, hypernatraemia, pericardial effusion and hypersomnia. The median time to onset of AEs associated with zanubrutinib was 51 days (IQR 13–192 days) and was consistent with the early failure model. In comparison with zanubrutinib monotherapy, the combination of zanubrutinib and rituximab therapy was linked to a higher risk of specific AEs, including myelosuppression, pneumonia, leucopenia, thrombocytopenia, abdominal pain, anaemia, pancytopenia and respiratory failure. Furthermore, the combination of zanubrutinib and chemotherapy increased the risk of several severe AEs, such as cardiac arrest, elevated blood lactate dehydrogenase levels and pancytopenia.Conclusions The results of the analysis provided valuable insights into the safety profile of zanubrutinib-treated patients, which was helpful for clinical monitoring and identifying potential AEs related to zanubrutinib.